Total Syntheses of (±)‐Aspidophylline A1. Issue 16 (5th March 2014) - Doris, Eric
<x xml:space="preserve">Abstract</x> Yes they can! The groups of Zhu and Ma recently reinvestigated the synthetic route to aspidophilline A. These approaches are discussed in the context of the first total synthesis of the title alkaloid that was reported by Garg and co‐workers in 2011.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>